DETERMINATION OF LOST FISHING GEAR IN THE INDLAND WATER OF TURKEY: SAMPLE OF KEBAN DAM LAKE (ELAZIG) - Dartay, Murside (Parlar Scientific Publications (P S P), 2021)
This study was detected the gross quantity of lost fishing gear in the indland waters of Turkey. We also consider ghost catches resulting from lost gear in other types of fisheries, and the extent to which the value of ghost catches has been quantified. By doing so. the study ultimately aims to contribute to reducing pollution by suggesting more efficient and practical management solutions for these problems. In fact,of all the thrown fishing nets found in the indland waters areas. 95 % are tramel-nets, gill-nets and traps. This study has indicated that gillnets, trammel nets and traps could be a considerable threat to indland water species once control of the nets has been lost. Using regression analysis it is that 4.4 km trammel nets, 7.2 km gill-nets and 500 set traps are lost gears annually. In conclusion; traditional fishing gears with ceo-friendly designs must and establishment of incentive programmes for the fishermen in the indland waters.
Keywords: Ghost fishing; lost gear; gillnets; trammel nets; traps; indland waters; Turkey